Studi Maqasyid Syariah As-Syatibi Terhadap Sistem Perkawinan di Indonesia - Muaidi; Jumain Azizi (TAFAQQUH, 2024)
This research examines the marriage system in Indonesia through the perspective of Maqasyid Syariah developed by Imam As-Syatibi. The main focus of the study is to analyze the extent to which the marriage system in Indonesia reflects and fulfills the five main objectives of Sharia (al-kulliyyat al-khams) according to As-Syatibi, namely the protection of religion (hifz ad-din), life (hifz an-nafs), intellect (hifz al-'aql), lineage (hifz an-nasl), and wealth (hifz al-mal). Using a qualitative approach with document analysis and literature study methods, this research reveals that the marriage system in Indonesia generally aligns with the principles of Maqasyid Syariah; however, several aspects need improvement to achieve a more optimal alignment. The research findings highlight the need to strengthen the protection of women and children, enhance pre-marital education, and refine the marriage dispute resolution mechanisms to better align with the principles of Maqasyid Syariah.